Effect of plant growth regulators and activated charcoal on in vitro growth and development of oil palm (Elaeis guineensis Jacq. var. Dura) zygotic embryo - Suranthran, Periasamy; Sinniah, Uma Rani; Subramaniam, Sreeramanan; Abdul Aziz, Maheran; Nordin, Romzi; Gantait, Saikat (Academic Journals, 2011)
The effect of plant growth regulators and activated charcoal (AC) on in vitro regeneration and plantlet development of oil palm (Elaeis guineensis Jacq. var. Dura) zygotic embryos were assessed. Zygotic embryos were cultured on Murashige and Skoog (MS) medium supplemented with a blend of 0.05 or 0.1 mg/L of each plant growth regulators (PGR) (gibberellic acid, 6-benzlaminopurine and α-naphthaleneacetic acid) without or with 2 g/L AC. The growth and development of the embryos were affected by the types of media formulations. Zygotic embryos cultured on MS medium supplemented with both PGR and AC enhanced shoot initiation and subsequent plantlet development, while PGR supplemented MS media without AC led to abnormal growth, suggesting that AC is indispensable for oil palm plantlet regeneration in vitro. The best medium for growth and development of plantlets was MS medium supplemented with 0.1 mg/L PGR and 2 g/L AC which significantly increased plantlet height (9.4 cm) as well as root length (4.4 cm) than the remaining media formulations.